2021
DOI: 10.51507/j.jams.2021.14.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile Response to Electroacupuncture in Non-Alcoholic Fatty Liver Patients with Hyperlipidemia

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) is estimated to be one of the most common diseases affecting the liver because of its high prevalence worldwide. Abnormal lipid profile between NAFLD patients has been reported in several studies. Objectives: This study aimed to evaluate the lipid profile response to electroacupuncture in NAFLD patients. Methods: A total of 60 female patients with NAFLD were included in the study with ages ranged from (30-55) years old. They were divided equally into two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Furthermore, specific acupoint stimulation amplifies the lipid-lowering effects by modifying inf lammatory markers (tumor necrosis factor-alpha and interleukin 6) and regulating lipid synthesis and conversion processes (inhibiting the conversion of FFA to TG and enhancing the conversion of proHDL to HDL). Several studies have corroborated these findings, highlighting the beneficial effects of acupoint stimulation on blood lipids [7,18,21,35].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, specific acupoint stimulation amplifies the lipid-lowering effects by modifying inf lammatory markers (tumor necrosis factor-alpha and interleukin 6) and regulating lipid synthesis and conversion processes (inhibiting the conversion of FFA to TG and enhancing the conversion of proHDL to HDL). Several studies have corroborated these findings, highlighting the beneficial effects of acupoint stimulation on blood lipids [7,18,21,35].…”
Section: Discussionmentioning
confidence: 78%
“…LAT was administered thrice weekly on selected acupoints according to traditional Chinese medicine principles [17]. Group A was treated at specific acupoints (GB34, GB28, ST25, ST36, ST40, SP6, CV4, CV9, and CV12) with a 2-minute laser at specific settings (a 2-J/cm 2 amplitude, 200-ns pulse period, 5000 Hz, and a 940-nm wavelength) [18][19][20][21][22].…”
Section: Latmentioning
confidence: 99%
“…The studies by Draz et al [14] and Taha et al [15] showed that patients with fatty liver who received electroacupuncture at LR14, LR3, ST36, and GB34 acupoints had a significant decrease in TG s levels. Another study conducted in 2018 reported that 8-week electroacupuncture treatment in obese patients' bilateral ST25 and GB28 acupoints significantly decreased their blood lipid levels [13].…”
Section: Discussionmentioning
confidence: 97%
“…Another study wherein Egyptian women with hyperlipidemia underwent 6-week electroacupuncture at the acupoints LR14, LR3, ST36, GB34 showed significant improvements in C, TG s , and LDL s levels among women who received the therapy at the real acupoints compared to those who did on fake acupoints [15].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation